Representasi Penghilangan Paksa melalui Majas dan Metafora dalam Novel Laut Bercerita - Rohmatulloh, Desy; Ani Rafika Sari; Mohamad Afrizal (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2026)
Enforced disappearance during the New Order era represents a historical reality that has left profound wounds and prolonged uncertainty for both the victims and the families left behind. This reality is powerfully represented in Laut Bercerita, a novel by Leila S. Chudori, through the use of symbolic and evocative literary language. This study aims to reveal the representation of enforced disappearance through the use of figures of speech and metaphors in the novel. The research employs a descriptive qualitative method with a stylistic approach. The data consist of narrative excerpts containing figures of speech and metaphors related to experiences of loss, suffering, memory, and resistance. Data collection was conducted through intensive reading and systematic note-taking, while data analysis involved classifying types of figures of speech and interpreting their contextual meanings. The findings indicate that metaphors of the sea, silence, darkness, and alienation play a crucial role in constructing the representation of enforced disappearance as a traumatic experience that is not only physical but also psychological and collective in nature. The use of figurative language strengthens the narrative’s expressive power in conveying criticism of state violence while simultaneously preserving the memory of humanitarian tragedies that are often marginalized. This study implies that literary works can function as reflective media and as cultural documentation of histories of violence.